STRATEGI PENGEMBANGAN USAHATANI UBI KAYU (Manihot utilissima) DI KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - I Wayan Hari Bakti Prabowo; Dwi Haryono; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The purpose of this study was to analyze internal factors, external factors and design development strategies that more appropriate for cassava farming. This study was conducted in two villages, namely Ujung Gunung Ilir Village and Kagungan Rahayu Village of  Menggala Subdistrict of Tulang Bawang Regency. This study uses census method involving 91 cassava farmers in the two villages. The method of analysis in this study are matrix of Internal Factors Analysis (IFAS),  matrix of External Factors Analysis (EFAS), and SWOT analysis. The results of the analysis of internal factors includes production and human resources for stregth component, also includes management, infrastructure, and organization for weaknesses component. The results of the analysis of external factors includes technology, demand, infrastructure, and land topographic for opportunities component, also includes another farming, the condition of weather and climate, price of cassava  for the threats component. The design of new strategies to develope this farm were: increasing production to fill the demand of tapioca and biofuel industry, optimizing the advanced mindset and environmental friendly, increasing economic activity for the welfare, improving the infrastructure to repair farm roads, and working efficiency to increase the competitiveness. Key words: cassava farming, development strategy, SWOT analysis